Electric Alignment of Plate Shaped Clay Aggregates in Oils - Castberg, René C.; Rozynek, Zbigniew J.; Flekkøy, Eirik G.; Måløy, Knut J. (Frontiers in Physics, 2016)
We experimentally investigate the rotation of plate shaped aggregates of clay mineral particles immersed in silicone oil. The rotation is induced by an external electric field. The rotation time is measured as a function of the following parameters: electric field strength, the plate geometry (length and width) and the dielectric properties of the plates. We find that the plates always align with their longest axis parallel to the direction of the electric field (E), independently of the arrangement of individual clay −2 mineral particles within the plate. The rotation time is found to scale as E and is proportional to the viscosity (μ), which coincides well with a model that describes orientation of dipoles in electric fields. As the length of the plate is increased we quantify a difference between the longitudinal and transverse polarisability. Finally, we show that moist plates align faster. We attribute this to the change of the dielectric properties of the plate due to the presence of water.